A Review on CNC Milling Parameter Optimization Using Taguchi and Response Surface Methodology (RSM) - Lase, Asaeli Tongoni; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
CNC milling technology is essential to today's industrial sector because it makes it possible to produce components precisely and efficiently. In this study, CNC milling machining parameters are optimized using the Taguchi technique and Response Surface Methodology (RSM). We also analyze several other characteristics such as Spindle Speed (SS), Feed Rate (FR), and Depth of Cut (DoC). To determine important factors and ideal configurations, this study blends statistical analysis, such as ANOVA, with experimental methods. According to the study's findings, the two most important variables affecting surface roughness (Ra) and Material Removal Rate (MRR) are FR and DoC. The optimization approach can help improve product quality while cutting down on production time. This in turn promotes the manufacturing process's efficiency.